Anterior/Apical single incision mesh (Elevate™): Surgical experience, anatomical and functional results, and long-term complications. (May 2021) - Faioli, Raffaele; Sozzi, Giulio; Chiantera, Vito; Maglione, Annamaria; Capozzi, Vito Andrea; Gadonneix, Pierre; Salet-Lizée, Delphine; Vincens, Etienne; Meschia, Michele; Villet, Richard
Highlights: MSV with Anterior/Apical single incision mesh Elevate™ is a well-tolerated procedure. High anatomical and functional success rate can be obtained. Short and long-term complications are acceptable and predominantly solvable. Abstract: Objective: Pelvic organ prolapse is a common condition among post-menopausal women, and surgery is often the standard treatment proposed. Native tissue vaginal surgery is burdened by a high rate of recurrence, and mesh vaginal surgery has become current practice. The purpose of this study was to evaluate the safety and the effectiveness of the vaginal kit Anterior/Apical single incision mesh Elevate™ for the correction of anterior and apical compartment prolapse. Study design: Data of patients with symptomatic anterior vaginal prolapse stage ≥ II, receiving mesh repair with the Anterior/Apical Elevate single incision system between January 2010 and January 2015 were retrieved. Prolapse was classified according to the POP-Q system. The main outcome measure was anatomical success, while subjective and safety outcomes were secondary outcomes. Results: Anatomical success rate was 87.2 % for anterior compartment prolapse and 84.6 % for combined anterior and apical prolapse, while overall functional success rate was 96.2 % after a median follow-up of 33.6 months. The most frequent short-term complications were urinary bladder injury (3.0 %) and transient urinary retention (6.9 %). The most common long-term complications were de novo or persistent symptomatic stress urinary incontinence (10.8 %) and vaginal mesh extrusion (3.8 %). Conclusion: Mesh vaginal surgery with Anterior/Apical single incision mesh Elevate™ is a well-tolerated procedure with a very high anatomical and functional success rate. Short and long-term complications rate seem to be acceptable, and in most of cases, solvable. Further studies are needed to confirm our promising data.